A Novel Biometric Fingerprint IT System in Determining Newborn Baby Identity - Lalović, Komlen (E-business technologies conference proceedings, 2025)
This work presents totally new IT security system and novel method for biometric verification for new born babies in birthplaces based on fingerprint minutiae. Information system realized combines nowadays program languages such as: Java, Python considering object-oriented languages, C programing language for device programming as structural (line) and SQL as relationship database management system to store encrypted data. RSA as asynchronous algorithm and key store value for encrypted fingerprint minutiae. Information system implementing device for biometric identification of maternity as dual fingerprint scanner that provides data of mother and baby fingerprints on very moment of birth and in further process guarantee maternity over new born baby with 100% accuracy, generating unique ID reference and encrypting those data with cancelable biometrics we developed totally novel method in determining identity based on baby fingerprint minutiae.